Doktrin Alkitab - Yulia Wulandari; Candra Junika; Yongki Pransoli; Cecen Cecen (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
Biblical doctrine is the theological foundation of the Christian faith. This research uses a library study method by reviewing various theological literature and the Bible as the main source. Biblical doctrine includes the concepts of the sufficiency, inspiration, and canonization of the Bible. Biblical sufficiency states that the Bible provides everything necessary for Christian faith and life, while biblical inspiration asserts that Biblical texts were inspired by the Holy Spirit. Bible canonization describes the process by which the books of the Bible are recognized as the authoritative Word of God. This research aims to strengthen understanding of Bible doctrine and emphasize the importance of returning to the Bible as the main source in Christian life.